2014
DOI: 10.1016/j.jhealeco.2014.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Forgetting to remember or remembering to forget: A study of the recall period length in health care survey questions

Abstract: Self-reported data on health care use is a key input in a range of studies. However, the length of recall period in self-reported health care questions varies between surveys, and this variation may affect the results of the studies. This study uses a large survey experiment to examine the role of the length of recall periods for the quality of self-reported hospitalization data by comparing registered with self-reported hospitalizations of respondents exposed to recall periods of one, three, six, or twelve mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
126
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(147 citation statements)
references
References 20 publications
5
126
1
7
Order By: Relevance
“…Data were obtained through patient or proxy report, although medical records were also used in Denehy et al 13 Hospitalizations occurring within 3 and 6 months can be self-reported with 98% and 96% accuracy, respectively. 45 Mortality data were not available in Elliott et al 14 Th e normed version of the SF-36 PF domain score, available in all studies, was used to assess responsiveness. Patient rating of global change in PF, administered at 6 and 12 months in the Denehy et al 13 trial, was also used in responsiveness analyses.…”
Section: Study Measuresmentioning
confidence: 99%
“…Data were obtained through patient or proxy report, although medical records were also used in Denehy et al 13 Hospitalizations occurring within 3 and 6 months can be self-reported with 98% and 96% accuracy, respectively. 45 Mortality data were not available in Elliott et al 14 Th e normed version of the SF-36 PF domain score, available in all studies, was used to assess responsiveness. Patient rating of global change in PF, administered at 6 and 12 months in the Denehy et al 13 trial, was also used in responsiveness analyses.…”
Section: Study Measuresmentioning
confidence: 99%
“…This relates to a removal of €1,317m of expenditure on services, which the HSE has defined as non-healthcare applying the SHA definition. The major excluded components relate to child services funded by the HSE in 2013 3 (€569m), superannuation (€181m), State Claims Agency (€135m) and exclusions related to allied healthcare professionals (€125m) 4,5 . It is noteworthy that little adjustment is made to account for social care services for older people and those with disabilities funded by the HSE which might be considered as non-healthcare services.…”
Section: Current Public Healthcare Expenditurementioning
confidence: 99%
“…One feature that varies greatly between different surveys is the period over which people are asked to recall expenditure [5] with a recent review of health surveys reporting that recall period can range from two weeks to 14 months with a significant proportion of surveys using either one or 12 months [6]. Different recall periods can give rise to different estimates of healthcare expenditure with Lu et al [7], for example, finding that a shorter recall period leads to a higher mean estimate of health spending.…”
mentioning
confidence: 99%
“…This result is consistent with previous studies on survey recall bias. For example, recall bias was observed to decrease for more educated survey respondents in various countries including India (Das, Hammer, and Sánchez-Paramo, 2012), Malaysia (Beckett et al, 2001), Sweden (Kjellsson, Clarke, and Gerdtham, 2014), and the US (Kennickell and Starr-McCluer, 1997). …”
mentioning
confidence: 99%